The Effectiveness of the Application of the Virtual Lab-Assisted ARIAS Learning Model on Motion and Force Materials in Improving the Cognitive Learning Outcomes of Grade VII Students of SMPN 1 Bangko Pusako - Ferdiansyah, Ferdiansyah; Irianti, Mitri; Ernidawati, Ernidawati (Universitas PGRI Semarang, 2025)
The low achievement of student learning outcomes is due to the lack of interest and activity of students in the learning process. Students do not understand the material and are not active during learning due to the monotonous learning model. This study is to describe and determine the effectiveness of the application of the ARIAS learning model combined with a virtual lab on motion and force materials in improving the cognitive learning outcomes of grade VII students of SMPN 1 Bangko Pusako. The study used a quasi-experiment approach with a Non-Equivalent Post-test Only Group Design. The sample consisted of two classes, namely the control class (28 students) and the experimental class (29 students). The research instrument is in the form of an objective test to determine students' cognitive learning outcomes. The data were analyzed through normality, homogeneity, and hypothesis tests. The results of the study stated that there was a significant difference in the cognitive learning outcomes of students in both classes. The average score of the experimental class was 71.7 (good category), and the control class got an average score of 53 (good category). After the Mann-Whitney U Test, a significance value of 0.000 (0.05) was obtained, so it was concluded that the virtual lab-assisted ARIAS model was effective in improving students' cognitive learning outcomes on motion and force materials.